2007
DOI: 10.1007/s10669-007-9036-5
|View full text |Cite
|
Sign up to set email alerts
|

Spray techniques: how to optimise spray deposition and minimise spray drift

Abstract: A summary is given of research within the field of application technology for crop protection products for the past 10 years in The Netherlands. Results are presented for greenhouse, orchard, nursery tree and arable field spraying for the typical Dutch situation. Research predominantly focussed on the quantification of spray deposition in crop canopy and the emissions into the environment, especially spray drift. The risk of spray drift is related to defined distances and dimensions of the surface water adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…However it should be noted that this conclusion regarding the soil cover is based on data from one author only. The interception values recommended by FOCUS (2002) were based on publications by Becker et al (1999), Ganzelmeier (1997 and Van de Zande et al (2000) and described in more detail by Linders et al (2000). The experimental field data referred to in these publications are limited.…”
Section: Correlation Between Soil Cover and Interceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However it should be noted that this conclusion regarding the soil cover is based on data from one author only. The interception values recommended by FOCUS (2002) were based on publications by Becker et al (1999), Ganzelmeier (1997 and Van de Zande et al (2000) and described in more detail by Linders et al (2000). The experimental field data referred to in these publications are limited.…”
Section: Correlation Between Soil Cover and Interceptionmentioning
confidence: 99%
“…The estimated interception values were compared against some field data from literature by Becker et al (1999). Linders et al (2000) compared some of the data against field data reported by Van de Zande et al (2000) but did not alter the estimated values. Some criteria and rules were used to estimate the interception values (personal communication Ton van der Linden).…”
Section: Correlation Between Soil Cover and Interceptionmentioning
confidence: 99%
“…According to the Chinese Civil Aviation Industry Standards, measuring droplet drift materials are usually polyethylene wire, glass, filter paper, water sensitive paper, chromatography and other methods. Many domestic and foreign experts and scholars researched on aerial spraying operation efficacy [18][19][20][21] . Some used water sensitive paper and mylar card to analyze the deposition parameters.…”
Section: Introduction mentioning
confidence: 99%
“…Generally, studies on spray characterization involve nozzles that are spraying vertically downwards, as it is the case for boom sprayers. However, in vineyards or in orchards, the liquid is sprayed horizontally, or even upwards, and may lead to more airborne drift than that in arable crops [7]. That is the reason why it would be worthwhile to assess spray nozzles in horizontal position as well as in vertical position.…”
Section: Introductionmentioning
confidence: 99%